History, theory, text : historians and the linguistic turn - Clark, Elizabeth A. (Elizabeth Ann), 1938- (Cambridge, Mass. : Harvard University Press, 2004)
"In this work, one of our foremost historians of early Christianity considers a variety of theoretical critiques to examine the problems and opportunities posed by the ways in which history is written. Elizabeth Clark argues for a renewal of the study of premodern western history through engagement with the kings of critical methods that have transformed other humanities disciplines in recent decades." "History, Theory, Text provides a user-friendly survey of crucial developments in nineteenth- and twentieth-century debates surrounding history, philosophy, and critical theory. Beginning with the "noble dream" of "history as it actually happened" in the works of some nineteenth-century historians, Clark goes on to review Anglo-American philosophies of history, schools of twentieth-century historiography, structuralism, the debate over narrative history, the changing fate of the history of ideas, and the impact of interpretive anthropology and literary theory on current historical scholarship. In a concluding chapter she offers some practical case studies to illustrate how attending to theoretical consideratios can illuminate the study of premodernity."--BOOK JACKET.
1. Defending and lamenting history -- 2. Anglo-American philosophy and the historians -- 3. Language and structures -- 4. The territory of the historians -- 5. Narrative and history -- 6. The new intellectual history -- 7. Texts and contexts -- 8. History, theory, and premodern texts.
Includes bibliographical references p. ([193]-318) and index.
Keywords: Historiography; History -- Philosophy; Christian literature, Early -- History and criticism